2021
DOI: 10.3390/en14092375
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Hydraulic Modelling and Experimental Validation of an Electro-Hydraulic Compact Drive

Abstract: Electro-hydraulic compact drives (ECDs) are an emerging technology for linear actuation in a wide range of applications. Especially within the low power range of 5–10 kW, the plug-and-play capability, good energy efficiency and small space requirements of ECDs render this technology a promising alternative to replace conventional valve-controlled linear drive solutions. In this power range, ECDs generally rely on passive cooling to keep oil and system temperatures within the tolerated range. When expanding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The cylinder power is obtained as the product of the measured actuation velocity and the loading force. The formula is given in Equation (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cylinder power is obtained as the product of the measured actuation velocity and the loading force. The formula is given in Equation (11).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the adoption of self-contained EHAs in off-road vehicles is challenged by the cost and space requirement, which in many cases requires modification of the mechanical structures. The thermal behavior of the self-contained EHA could be another concern based on some previous studies [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the temperatures of the two thermocouples were very similar to each other for every power level, indicating a high rate of heat transfer from the pump housing to the fluid being pumped. Ketelsen et al [19] used a similar approach which lumped the thermal capacitances of multiple components including the pump, motor, and oil to predict the temperature of a larger EHA system with accuracy suitable for design purposes. The metal compression fitting conducts heat from the pump housing very well and appears to reach temperatures near that of the pump housing, as shown in Figure 2a.…”
Section: Thermal Performance Resultsmentioning
confidence: 99%
“…Since throttling losses are supposed to be small in pump-controlled systems, the need for cooling is much smaller compared to conventional valve-controlled systems, but it may still be required. Ketelsen et al has analysed the thermal properties and concluded that passive cooling may be sufficient for a power range of 5-10 kW [86].…”
Section: Auxiliary Functionsmentioning
confidence: 99%